A user-aware approach for describing and publishing context aware composite Web service. Issue 2 (6th June 2016) - Cherif, Sihem; Ben Djemaa, Raoudha Ben; Amous, Ikram
Abstract : Purpose: The purpose of this paper is to describe the composite service and the context properties related to the users in the business process execution language (BPEL) file. Design/methodology/approach: The authors' approach allows expressing requirements by taking into account potential users' context in addition to the functional one. Findings: In this paper, the authors introduce a new context-aware approach that provides a dynamic adaptation of service compositions. Originality/value: This paper introduces a user-aware approach for describing and publishing context-aware composite Web service.